TINGKAH LAKU SISWA SEKOLAH DASAR FULL DAY SCHOOL ISLAM TERPADU QARDHAN HASANAH DI KOTA BANJARBARU - Tati'ah (Universitas Achmad Yani Banjarmasin, 2018)
Every individual takes time to absorb the material to be learned, the learning time is the time that students use to learn good and appropriate according to their situation. So the time in learning needs to be tailored specifically to be more efficient in achieving the target learning. The full day school system is a school that runs the teaching and learning process throughout the day or is enforced from the morning until the afternoon, with the duration of rest every two hours. Subjects that are difficult to place in the morning and easier subjects are given in the afternoon. Learning regularity is the mainstay of good learning for high personal discipline students can stay away from temptations and distractions that encourage lazy students to learn. Given the full day school policy, it is expected that children's achievement will improve or affect their behavior at home and at school. This research has a purpose to know behavior of elementary school student of Iswami Integrated Islamic School Day Qarshan Hasana in Banjarbaru city. As for the object in this research is the behavior of students of Elementary School full day school Islami Integrated Qardhan Hasana di Banjarbaru city and the subject of research is allstudents of VB grade SDN Islami Integrated Qardhan Hasana city in Banjarbaru. This research uses quantitative descriptive method and the tool used to extract the data behavior of students of elementary school full day school Islami Integrated Qardhan Hasana in Banjarbaru city in this study is questionnaire. Population in this research isall students in SDN Islami Integrated Qardhan Hasana in Banjarbaru city which amounts to 547 people and sampling technique using purposive sampling technique so that the sample in this research is VB students of 35 people. Based on the results of the research that has been proposed, the researcher can conclude that, it is known that the emotional behavior of students such as the development of intelligence and responding to the situation, students who always say as much as 57.41%, the behavior of the use of technology that includes the use of technology in schools and activities that exist in schools, students who always say as much as 48.15%, student behavior on the environment such as interaction with friends, interaction with teachers and others, and interaction with family, students who always say as much as 49.53% student behavior in school activities both in learning and playing activities, students who stated always as much as 68.52%.